2018
DOI: 10.21608/aprh.2018.5173.1063
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Livistona decipiens Leaf Methanol Extract and Evaluation of Antioxidant, Antimicrobial and Cytotoxic Activities

Abstract: Objectives: This study aimed to isolate the polyphenolic constituents from the methanol extract of Livistona decipiens Becc leaves and evaluate the antioxidant, cytotoxic and antimicrobial activities of the total methanol extract and ethyl acetate fraction. Methods: The ethyl acetate and n-butanol fractions of Livistona decipiens leaf methanol extract were subjected separately to different chromatographic separation techniques. Structures of the isolated compounds were established by different spectroscopic te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…The least total flavonoid contentwas detected with petroleum ether extract (6PL) (18.27 ± 0.0.21 mg QE/g). These results are in agreement with that previously reported, 29 where it was found that the polarity of the extraction solvent increases the quantities of the flavonoids extracted. © 2021 the authors.…”
Section: Quantitative Analysis Of the Phytochemicalssupporting
confidence: 94%
See 2 more Smart Citations
“…The least total flavonoid contentwas detected with petroleum ether extract (6PL) (18.27 ± 0.0.21 mg QE/g). These results are in agreement with that previously reported, 29 where it was found that the polarity of the extraction solvent increases the quantities of the flavonoids extracted. © 2021 the authors.…”
Section: Quantitative Analysis Of the Phytochemicalssupporting
confidence: 94%
“…The least antioxidant activity is represented in the petroleum ether extract (6PL). These results are in agreement with that reported for P. daemia, 29 as it proved that, the ethanol extract followed by ethyl acetate shows a very close antioxidant activity when compared with the standard, and the least antioxidant activity was exhibited in the n-hexane, and humans can eliminate the free radicals and get relief from oxidative stress effectively by consuming P. daemia even at low concentration. The redox properties of the phenolic compounds play a key role as antioxidants or free radical scavengers which can absorb and neutralize free radicals, triplet oxygen or decomposing peroxides.…”
Section: Quantitative Analysis Of the Phytochemicalssupporting
confidence: 92%
See 1 more Smart Citation
“…Traditionally they have been utilized as analgesics and for leukemia, esophageal cancer and nasopharyngeal carcinoma 4 . Reviewing the current literature, it was found that plants belonging to genus Livistona are rich in flavonoids, triterpenes, alkaloids, phenolic acids, amino acids and fatty acids [5][6][7][8][9][10] . In this study, the aqueous ethanolic extract of L. chinensis leaves were qualitatively and quantitatively characterized for the first time by HPLC-PDA-MS/MS, and the total extract was assessed for its anticancer activity.…”
Section: Introductionmentioning
confidence: 99%
“…The phenolic acids derived from benzoic acid; 2-hydroxy benzoic acid (salicylic acid) (8) and 3,4-dihydroxy benzoic acid (protocatechuic acid) (10) presented pseudomolecular ions at m/z 137 and 153, respectively. Their retention times and mass fragmentations proved their identification, based on reference samples.…”
Section: Benzoic Acidsmentioning
confidence: 99%